Inclusive breakup measurements of the 7Li+ 119Sn reaction. (December 2020) - Fernández-García, J. P.; Alvarez, M. A. G.; Cherubini, S.; Di Pietro, A.; D'Agata, G.; Fernández, B.; Figuera, P.; Fisichella, M.; Giulino, M.; La Cognata, M.; Lamia, L.; Lattuada, M.; et al.
Abstract: We present preliminary data of elastic scattering and inclusive breakup cross sections for the 7 Li+ 119 Sn reaction, recently measured at the Laboratori Nazionali del Sud (LNS-INFN) (Catania, Italy) at energies around the Coulomb barrier (E lab = 21.2 and 26.5 MeV). The experimental data have been analyzed under the Optical Model and Continuum-Discretized Coupled-Channels methods.